Al-Rahmah Dalam Al-Qur’an (Suatu kajian Tematik) - Muhammad Nur Abduh (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2015)
This article studies about the meaning of rahmah that was written repeatedly in many chapters. Rahmah is considered as great mission shouldered by the Great prophet Muhammad saw, who become good example for believers to realize the balance, peace and the true love and affection. Rahmah is a quranic term pointing out the God’s attributes who always keep love and affection and bestows His grace on human being.